Social Policy Analysis in Addressing Economic Inequality: Evaluating Effectiveness, Challenges, and Policy Implications - Arnold Caledon (Kampret Journal, 2026)
Economic inequality remains a critical challenge in many countries, reflecting disparities in income distribution, access to resources, and opportunities for social mobility. This study aims to analyze the role and effectiveness of social policies in addressing economic inequality, focusing on key policy areas such as poverty alleviation programs, education, healthcare, labor and wage regulations, and taxation and redistribution systems. The research adopts a mixed-methods approach, combining quantitative analysis of inequality indicators such as the Gini coefficient, poverty rates, and Human Development Index (HDI) with qualitative analysis of policy documents and implementation practices. The findings indicate that social policies have a positive but uneven impact on reducing economic inequality. Short-term interventions, such as cash transfer programs, are effective in alleviating immediate poverty, while long-term policies in education and healthcare contribute to human capital development and improved economic opportunities. However, the overall effectiveness of these policies is constrained by several challenges, including corruption, mis-targeting of beneficiaries, limited funding, and weak institutional coordination. This study also reveals a gap between expected and actual policy outcomes, highlighting the importance of effective implementation and governance. The research concludes that while social policies are essential tools for reducing inequality, their success depends on integrated, well-targeted, and sustainable approaches. Strengthening policy design, improving transparency and accountability, and prioritizing long-term structural reforms are necessary to enhance their impact. This study contributes to the understanding of how social policies can be optimized to promote inclusive and equitable socio-economic development.